Identification of molecular patterns and diagnostic biomarkers in juvenile idiopathic arthritis based on the gene expression of m6A regulators - Zhang, Shibo; Qin, Jing; Zhao, Yuechao; Wang, Jian; Tian, Zhiliang (Frontiers in Pediatrics, 2022)
The role of N6-methyladenosine modification in immunity is increasingly being appreciated. However, the landscape of m6A regulators in juvenile idiopathic arthritis (JIA) is poorly understood. Thus, this study explored the impact of m6Amodification and related lncRNAs in JIA immune microenvironment. Fourteen m6A regulators and eight lncRNAs were identified as potential diagnostic biomarkers for JIA. Two diagnostic models for JIA were also constructed. The putative molecular regulatory mechanism of FTO-mediated m6A modification in JIA was hypothesized. Three distinct m6A patterns mediated by 26 m6A regulators and three diverse lncRNA clusters mediated by 405 lncRNAs were thoroughly investigated. They exhibited dramatically diverse immune microenvironments and expression of HLA genes. The identification of two separate subtypes of enthesitis-related arthritis implies that our work may aid in the establishment of a more precise categorization system for JIA. m6A modification-related genes were obtained, and their underlying biological functions were explored. The m6Ascore system developed for individual JIA patients may be utilized to evaluate the immunological state or molecular pattern, thereby offering therapy recommendations. In short, through the investigation of the m6A regulators in JIA, the current work may contribute to our knowledge of the pathophysiology of JIA.